Study on the Perception of Knowledge of Nutrition like Protein - Pratima Dagar; V.K Sharma (Journal of Biomedical and Pharmaceutical Research, 2023)
Nutrition refers to the process through which an organism takes in and uses food to meet its metabolic requirements. The main aim of the study is Study on The Perception of Knowledge of Nutrition Like Protein. The five-motor ability test was used to evaluate the research population’s fitness, and their nutritional condition was determined before the questionnaire was given out. Understanding the importance of diet in improving athletic performance is crucial. An athlete’s performance in a competition may be affected by a wide variety of circumstances, each of which may have its own root cause. Keywords: Nutrition, Knowledge, Athletes, Performance, Metabolic